Engineering apoferritin for targeted delivery of peptides or proteins for the treatment of breast cancer - Ferreira, Lenny (2023)
Ferritin is a universal intracellular protein that stores iron and accounts for the majority of iron storage in the body. Ferritin is produced by almost all living organisms, including archaea, bacteria, algae, higher plants, and animals. Human ferritin is comprised of 24 subunits, which can self-assemble into a protein cage above pH 4.5. Human apoferritin, which is ferritin void of its iron core, has many characteristics that make it favourable as a drug delivery system: its biocompatibility: its biodegradability: and its capacity for spatially defined multivalent ligand display. The major focus of this PhD study is targeted delivery of human heavy chain apoferritin to breast cancer cells. The study initially focused on removing the ferroxidase ability of human heavy chain apoferritin (human heavy chain apoferritin 222). This is because highly reactive hydroxy radicals are produced during ferroxidation. Given that there is a risk that hydroxy radicals could affect encapsulated payloads, it was essential that this function be removed. Following removal of the ferroxidase residues, circular dichroism and native polyacrylamide gel electrophoresis showed no major changes to both the secondary and tertiary structure compared to its parent human heavy chain apoferritin. Kinetic studies of human heavy chain apoferritin 222 showed a slower iron core formation time than its parent protein. Following this, potential residues on human heavy chain apoferritin that could be involved in transferrin receptor 1 receptor binding were identified. Human heavy chain apoferritin has the innate ability to target transferrin receptor 1, a membrane protein expressed on most normal cells and overexpressed in many cancers, including breast cancers. However, this innate ability can cause problems when human heavy chain apoferritin is primed with other ligands, e.g., affibodies, for targeting alternative biomarkers such as the human epidermal growth receptor 2. One of the possible issues when attaching new targeting ligands is where secondary non-specific uptake by transferrin receptor 1 is undesirable. Therefore potential residues along the BC loop that could be involved in transferrin receptor 1 binding were removed (giving the TfR- mutant). A mutant cysteine residue was also introduced in the interior of human heavy chain apoferritin for conjugation of fluorescent probes. Maleimide conjugation of fluorescent probes was achieved using 8 M urea to disassemble the apoferritin cage and make the cysteine accessible. The tagged apoferritin was then evaluated by confocal microscopy, and results indicated that TfR- was not taken up by SKBR3, a high transferrin receptor 1 expressing breast cancer cell line. Reduced uptake by TfR- confirmed that mutations along the BC loop (residues 80-82) considerably reduce uptake of human heavy chain apoferritin via transferrin 9 receptor 1 receptor. This finding was quantitatively confirmed using flow cytometry. To evaluate the effect of a new targeting ligand on human heavy chain apoferritin on transferrin receptor 1 binding, human epidermal growth factor receptor 2 targeting ligand (affibody) was engineered onto the N-terminus of the apoferritin subunits. Native polyacrylamide gel electrophoresis analysis confirmed that the targeting ligand did not affect the tertiary structure or assembly of human heavy chain apoferritin. Homology modelling studies of affibody-human heavy chain apoferritin indicated only partial obstruction of the transferrin receptor 1 receptor binding site by the affibody ligand. Flow cytometry studies using breast cancer cell lines BT474 (HER2+), SKBR3 (HER2+), MDA-MB-231 (HER2 normal) and MDA-MB-468 (HER2-) showed that the addition of affibodies onto human heavy chain apoferritin does not obstruct transferrin receptor 1 binding completely.